Implementasi Rumah Lamin Pada Pusat Kesenian Suku Dayak di Kota Samarinda - Alessandra Monica Putri H Suprayitno; Laksmi Kusuma Wardani; Stephanie Melinda Frans (Intra, 2018)
Samarinda is the capital city of East Borneo (East Kalimantan). It currently requires a place for Dayak Tribes artists to express themselves and to be an art center at the same time. This art center is also intended as an art appreciation and education facility, tourist destination, as well as become a new icon for Samarinda city. For this several reasons, the designer designed “Samarinda Dayak Tribes Art Center”. The purpose of this art center is to facilitate Dayak Tribes art activities and become a recreational place for local and foreign tourist in order to increase the local economic income. The design method is design thinking which includes some steps such as Empathize, Define, Ideate, Prototype, and Test. Interior concept in the design aims to show the facility as a home for Dayak Tribes Art by using Rumah Lamin concept.